Associations between smoking status and involvement of personal and professional relations among individuals reporting symptoms related to a diagnosis of lung cancer: a population-based study - Frederik Vognsgaard; Lisa Maria Sele Sætre; Sanne Rasmussen; Dorte Ejg Jarbøl (BMC, 2022)
Abstract Background Smoking is the leading cause of lung cancer, but individuals who currently smoke seek healthcare less frequently. This study of individuals reporting symptoms related to diagnosis of lung cancer has the following aims: 1) to explore the involvement of personal and professional relations; 2) to analyse whether age, sex and smoking status are associated with involving personal and professional relations; and 3) to analyse whether involving a personal relation is associated with healthcare-seeking. Methods Data was extracted from a Danish population-based survey from 2012 with 100,000 randomly selected invitees 20 years or older. We describe the involvement of personal and professional relations among individuals experiencing four predefined symptoms indicative of lung cancer: prolonged coughing, prolonged hoarseness, shortness of breath and haemoptysis, either alone or in combination. Using multivariate logistic regression, we analyse the associations between involving personal or professional relations and various covariates (sex, age, smoking status). Moreover, we analyse the association between involving a personal relation and healthcare-seeking. Results A total of 35,958 individuals over 40 years old completed the questionnaire. Of these, 5,869 individuals reported at least one lung cancer symptom. A higher percentage of participants with prolonged hoarseness and prolonged coughing reported no involvement of personal and professional relations (27.6% and 22.7%, respectively) compared to shortness of breath (12.4%). The most involved personal and professional relations were the spouse (46.2-62.5%) and the general practitioner (GP) (31.3-54.5%), respectively. Women and individuals in the oldest age group had higher odds of involving personal and professional relations. Individuals who currently smoke involved all relations less frequently than individuals who formerly,- and never smoked. Odds of contacting the GP or another doctor were three to seven-fold higher when a personal relation was also involved. Conclusion Women and the oldest age group had higher odds of involving relations, whereas individuals who currently smoked tended to be less likely to contact any personal or professional relations. Involving a personal relation was associated with higher odds of healthcare-seeking. The findings could be useful for GPs in terms of identifying patients at risk of postponing relevant healthcare-seeking with potential lung cancer symptoms.